TIC10/ONC201—a potential therapeutic in glioblastoma - Karpel-Massler, Georg; Siegelin, Markus D. (Translational Cancer Research, 2017)
Glioblastoma represents the most frequent primary brain tumor in adults and despite great efforts it remains to be an incurable disease.